Partispasi Bermakna Dalam Formulasi Kebijakan Publik: Studi Mengenai Proses Legislasi Rancangan Undang-Undang Masyarakat Hukum Adat Tahun 2018-2023 - Yosia Viera Martua Sianturi; Alamsah Deliarnoor, Nandang (Dinasti Review Publisher, 2024)
Indegenous Law Peoples have always been marginalized with growing of time. A special law is needed to address problems among customary law communities. The establishment of Law Indigenous Peoples has actually started since 2014 under the name of the PP-MHA and change into the MHA in 2019. Currently MHA Bill is in the national legislation and waiting schedule for the discussion. This research aims analyze the legislative process of MHA Bill using model of policy formulation and concept of meaningful participation. This research uses qualitative methods with exploratory approach and case study strategy. The results are. First, problems among customary law communities are mostly caused by legal uncertainty. Sectoral laws who regulate indegenous law communities different from one another. Second, the stage of selecting alternative policies, there is conflict of interest between factions debating of development and investment will be disrupted because the birth of this Law. Third, the main reason MHA Bill has not been passed, is there are no political will from President and DPR RI to pass MHA Bill. Finally, public participation cannot be said to be meaningful participation. This is caused lack of public access related to conveying aspirations, considering aspirations, and explaining aspirations.